A phenomenological inquiry into the lived experience of adults diagnosed with attention deficit hyperactivity disorder (ADHD) employed by the NHS. Issue 2 (4th February 2021) - Rowe, Kayte Jayne; Bailey, Sarah; Teague, Bonnie; Mattless, Kevin; Notley, Caitlin
Abstract : Purpose: Approximately 3.5% of the workforce is diagnosed with attention deficit hyperactivity disorder (ADHD). With a greater risk of work-related stress and absences, work-based social interactions and environments are significant factors. The purpose of this study was to identify the professional challenges and benefits of living with ADHD in healthcare settings. Design/methodology/approach: Interpretative phenomenological analysis was used to explore how employees with ADHD both experience and make sense of their employment and professional relationships. Participants self-identified from two NHS trusts and participated in semi-structured interviews. Findings: A total of seven interviews contributed to the final analysis. A total of four themes emerged: social environment (relationships), physical environment, behaviour and work tasks. Complex interactions were observed between individuals' internal constructs and overall employment experience. Practical implications: The findings can be used to inform local NHS management frameworks for supporting workforce with ADHD. Originality/value: This is a novel study that explores the psychodynamic and physical presentations of ADHD providing a unique perspective on the challenges and strengths of employees with ADHD.